2014
DOI: 10.14260/jemds/2014/3941
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Diabetic Foot in Diabetics With Micro and Macrovascular Complications

Abstract: A complete general and systemic examination to be carried out on diabetic subjects, analysing their micro and macrovascular complications and evaluating their risk of developing diabetic foot. Data analysis was done by calculating the p-value using the Chi Square Test. RESULTS: Out of 200 patients, 12 were at a high risk of developing diabetic foot, while 57 and 131 were at low and moderate risk respectively. Demographic profile revealed a higher risk among the older population (p=0.0003), low Socioeconomic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…The overall proportion of DFU risk was higher among men than women. Previous studies7 20 23 30 have also reported similar findings. However, a community-based study from India reported that DFU risk was high in women,24 which is contradictory to our finding.…”
Section: Discussionsupporting
confidence: 82%
“…The overall proportion of DFU risk was higher among men than women. Previous studies7 20 23 30 have also reported similar findings. However, a community-based study from India reported that DFU risk was high in women,24 which is contradictory to our finding.…”
Section: Discussionsupporting
confidence: 82%